Egyptian Equity Market between International Integration and Segregation - Haikal, Gamal; Barakat, Mahmoud Ramadan (International Journal of Economics and Financial Issues, 2019)
The purpose of this paper is to investigate the degree to which the Egyptian capital market is integrated to the international markets approximated by the U.S. market. The study used Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) tests that considers possible structural fracture and trend in the time series Empirical results deduced from the Johansen-Juselius (JJ) efficient approach shows that the Egyptian market in the Long-run is segmented internationally. This gives a signal to the international portfolio managers that the Egyptian capital market represents a good opportunity for international diversification. Especially with a growing evidence of the integration of the international markets. Results indicated that there is no long run of short run causal relationship between the two indices under investigation. The researches have studied the Egyptian capital market after 2011 revolution which represents a milestone in the Egyptian history, resulted in a large economic and social changes. Specially that the relationship between the capital markets is dynamic. Keywords: emerging economies, stock market, co-integration. JEL Classification: G DOI: https://doi.org/10.32479/ijefi.7525